Pengaruh Intangible Asset dan Profitabilitas terhadap Tax Avoidance dengan Transfer Pricing sebagai Variabel Moderasi - Bagus Aditya, Ade; Nuryati, Tutty; Rossa, Elia; Puspaningtyas Faeni, Dewi; Manrejo, Sumarno (CV. Lafadz Jaya, 2023)
The aim of this research is to analyze theories explaining intangible assets, profitability, and transfer pricing in relation to tax avoidance. This study employs a quantitative approach through a literature review method. It presents the theoretical foundation, other explanatory variables, and findings from previous research. The research is grounded in agency theory and stakeholder theory. The supporting variables influencing tax avoidance consist of intangible assets and profitability, with transfer pricing serving as a moderating variable. The results indicate the influence of intangible assets and profitability on tax avoidance, as well as the moderating effect of transfer pricing on the relationship between intangible assets, profitability, and tax avoidance. This study aims to provide insights into understanding the observed phenomena.